Sanksi HukumTerhadap Pernikahan Melangkahi Dalam Adat Jawa Perspektif Hukum Islam - Wahidah, Wahidah; Sirait, Adi Syahputra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The focus of this research is the legal sanction for overstepping marriage in Javanese custom from the Perspective of Islamic Law in Labuhan Labo Village, Padangsidimpuan Tenggara District. The research method used is field research with a qualitative approach. .primary data sources, namely research data sources obtained directly from the original source in the form of interviews with the village head, traditional leaders and the community who received the sanction, there were 9 couples in Labuhan Labo Village, while secondary data could be in the form of books, journals, .as well as other supporting sites or resources.data collection technique that is by doing 3 methods in this study, namely by way of interviews, observation, and documentation. .The data analysis technique in this study is descriptive qualitative.The results of this study indicate that the legal sanctions for Steps in Javanese marriages in Labuhan Labo Village, Padangsidimpuan Tenggara District, namely sengadek (a set of clothes), carry out these sanctions when surrendering. .Thus there is the word of Allah in Al-Qur'an Surah An-Nur 32-33 and as for the conditions for marriage in Islamic law there is no condition for marriage until it is permitted by his brother, but because in Javanese custom it is a condition for marriage when you want to step over your brother nya, then society.apply these rules.